Dominant Factors Associated with Low Birth Weight in Newborn - Eva Arisandhy; Dyah Woro Kartiko Kusumo Wardani; Dewi Novitasari Suhaid; Putu Sukma Megaputri; Luh Ayu Purnami; Lina Anggaraeni Dwijayanti (Politeknik Kesehatan Kementerian Kesehatan Semarang, 2023)
The leading causes of neonatal or neonatal death in the world according to WHO, 2015 are low birth weight (LBW) 29%, sepsis and pneumonia 25%, asphyxia and trauma 23%. The incidence of BBLR in Blahbatuh II UPTD increased from 2017 to 2019. This study aims to determine the dominant factors associated with the incidence of LBW in the UPTD Puskesmas Blahbatuh II workspace. This study used an observational analytical design through a cross-sectional approach. The data used are secondary data from a retrospective cohort. The population of this study was all mothers born in the UPTD Puskesmas Blahbatuh II work area in 2019, a total of 137 respondents. Sampling technique with Total Sampling. Data analysis in this study used the chi-square test to prove the association of the factors causing LBW and multiple logistic regression tests to determine the most influential factors on the incidence of LBW. The results showed a significant association for 2 variables, antenatal examinations and nutritional status during pregnancy, while the variables maternal age, gestational distance, parity, Hb levels and maternal education have no significant association with the incidence of LBW. Multivariate analysis showed that the most important factor between nutritional status during pregnancy and ANC visits affecting LBW in the UPTD Puskesmas Blahbatuh II workspace was nutritional status during pregnancy. The Anova analysis test showed that the effect of nutritional status on LBW is 66.67% and the effect of ANC visits is 2.71%. It can be concluded that maternal nutritional status affects LBW more than ANC visits.